Permeation through graphene ripples. (1st February 2017) - Liang, Tao; He, Guangyu; Wu, Xu; Ren, Jindong; Guo, Hongxuan; Kong, Yuhan; Iwai, Hideo; Fujita, Daisuke; Gao, Hongjun; Guo, Haiming; Liu, Yingchun; Xu, Mingsheng
Abstract: Real graphene sheets show limited anti-permeation performance deviating from the ideally flat honeycomb carbon lattice that is impermeable to gases. Ripples in graphene are prevalent and they could significantly influence carrier transport. However, little attention has been paid to the role of ripples in the permeation properties of graphene. Here, we report that gases can permeate through graphene ripples at room temperature. The feasibility of gas permeation through graphene ripples is determined by detecting the initial oxidation sites of Cu surface covered with isolated graphene domain. Nudged elastic band (NEB) calculations demonstrate that the oxygen atom permeation occurs via the formation of C–O–C bond, in which process the energy barrier through the rippled graphene lattice is much smaller than that through a flat graphene lattice, rendering permeation through ripples more favorable. Combining with the recent advances in atoms intercalation between graphene and metal substrate for transfer-free and electrically insulated graphene, this discovery provides new perspectives regarding graphene's limited anti-permeation performance and evokes for rational design of graphene-based encapsulation for barrier and selective gas separation applications through ripple engineering.